2020
DOI: 10.3390/su12093858
|View full text |Cite
|
Sign up to set email alerts
|

Flat Glass or Crystal Dome Aperture? A Year-Long Comparative Analysis of the Performance of Light Pipes in Real Residential Settings and Climatic Conditions

Abstract: This paper presents the first comparative study of its type of the performance of light pipes with different types of apertures: a flat glass versus a bohemian crystal dome. Measurements were taken at 20-minute intervals over a period of one year in the bathrooms of two newly built identical houses of the same orientation located in Manchester, UK. The comparative analysis of the data collected for both light pipes types reveals that the crystal domed aperture consistently outperforms the flat glass one. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
0
0
Order By: Relevance
“…A diamond-shaped dome for the collector captures more light than a simple dome and this was proved in this study [58]. Also a comparison between the flat and crystal dome collectors, which is done by M. Sibley and A. Peña-García [59]; The crystal dome allows transmit a higher luminous flux than a flat glass in the colder months of the year (winter), this rate increases even more; As a result, the crystal dome performs better than flat glass, especially when pollution and effects of weathering are involved in the analysis, moreover for this crystal dome cover, antireflective glass with a high transmittance coefficient is recommended. Radiance properties of materials for light pipes in our case study are shown in Table 3.…”
Section: Modeled Light Pipe Descriptionsupporting
confidence: 59%
“…A diamond-shaped dome for the collector captures more light than a simple dome and this was proved in this study [58]. Also a comparison between the flat and crystal dome collectors, which is done by M. Sibley and A. Peña-García [59]; The crystal dome allows transmit a higher luminous flux than a flat glass in the colder months of the year (winter), this rate increases even more; As a result, the crystal dome performs better than flat glass, especially when pollution and effects of weathering are involved in the analysis, moreover for this crystal dome cover, antireflective glass with a high transmittance coefficient is recommended. Radiance properties of materials for light pipes in our case study are shown in Table 3.…”
Section: Modeled Light Pipe Descriptionsupporting
confidence: 59%
“…The Special Issue, entitled "The Future of Interior Lighting Is Here", addressed several subjects on interior lighting such as architectural lighting, daylighting, Human Centric Lighting (HCL), the impact on human health, lighting design, sustainability, and social impact and wellbeing. A total number of eleven articles, ten research papers [24][25][26][27][28][29][30][31][32][33] and one review paper [34], were published. In terms of the geographical distribution of the affiliations of the 34 contributing authors, contributions originated from ten countries, including Austria, Denmark, France, Germany, Korea, Slovakia, Spain, Sweden, Tunisia, and UK.…”
Section: Methodsmentioning
confidence: 99%
“…Sibley and Pena-Garcia [33] presented a comparative study concerning the performance of light pipes with two different types of apertures. A bohemian crystal dome was compared to a flat glass.…”
Section: Daylightmentioning
confidence: 99%
“…Tsangrasoulis et al [12] have undertaken studies in order to examine a hybrid system of natural light, while Doulos et al [13] investigated the correlation between dimming and natural light hybrid systems, whereas Kontadakis et al [14] concentrated on the effect of dynamic daylight redirection systems. In addition to the above, various studies have been carried out on the research into daylighting systems within various types of buildings, and their results [15][16][17][18] provide evidence and scope to integrate these elements into a holistic approach towards an example design. If daylight design is left unchecked, it can create negative conditions in terms of the individual energy characteristics of the proposed solution to heating and cooling needs.…”
Section: Introductionmentioning
confidence: 99%